Feature Extraction Using Pulse-Coupled Neural Network in Isolated Speech Recognition - Matus Jurecka (Communications - Scientific letters of the University of Zilina, 2006)
This article presents achieved results concerning an feature extraction in isolated speech recognition problem using the Pulse-Coupled Neural Network (PCNN) approach. PCNN based feature extraction is analyzed for a direct Pulse Coded Modulation (PCM) input and a Fast Fourier Transform (FFT) coefficients input.